Rice based cropping systems for enhancing productivity Decadal experience of AICRIP - Tuti, Mangal Deep; Kumar, R Mahender; Sreedevi, B; Saha, Soumya; Singh, Aarti (Indian Farming, 2019)
While most rice is grown in the kharif (wet-season, roughly July–December), rice is also grown in the rabi (dry-season, roughly January–June) in many states. Approximately 55% of India’s rice crop is irrigated, up from about 45% in 1990; the fraction of rice area that is irrigated varies by state from <50% in Madhya Pradesh, Maharashtra and Bihar, to >90% in Punjab, Tamil Nadu, Andhra Pradesh, and Haryana. Existing All India Coordinated Rice Improvement Project at ICAR-IIRR, Hyderabad, India provides sufficient information on the decadal changes in the cropping systems research, further to quantify and reach a future novel research strategy to enhance productivity of rice based cropping systems.